UPAYA MENINGKATKAN PENDAPATAN USAHA PADA USAHA MIKRO KACANG DISCO KECAK MAMA - Puspitawati, Ni Made Dwi; Paramita, Ida Ayu Putu Utami; Praganingrum, Tjokorda Istri (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2017)
The increasingly fierce competition market requires an entrepreneurto always innovate on their products so that their sales can undoubtedly be top of the market line. Kacang Disco Kecak Mama is one of the micro enterprises that is available and  ready to win the hearts of peanut lovers. This company often uses their peanuts as souvenirs, which is a highy sought after consumer product in Bali. They offer a variety of flavors such as original flavor, super spicy, cheese, barbeque, pizza, squid, shrimp, grilled fish, milk egg honey, and soybean. The name of Kacang Disco Kecak Mama comes from the founding enterpreneur?s hobby of enjoying ?disco?, and the other part of the name ?kecak? derived from the kecak dance which is a typical traditional Balinese dance and the last part ?mama? comes from the desire of the entrepreneurto always have his mother?s blessing so that his endeavors always run smoothly. Twenty five employees are able to produce 250kg, which correlates to about 500kg of Disco Kecak Mama after processing. Some weaknesses in the promotion system, the shortage of electric scales in packaging and the layout of the packaging space. These weakness create a limited barrier to the entrepreneural company. A shortage in these areas make it difficult to work more efficienty and produce a larger mass product. In accordance with the problems faced by entrepreneur, we have created several solutions to offer that would make the business Kacang Disco Kecak Mama more advanced. Here are the following solutions created : (1) an advanced online tactical system either through website or social media (facebook and instagram) so as to reach consumers wordwide (2) create a neon box as a means to introduce this effort to the community, (3) electrical scales for product consumtion, this increases efficiency so that the entrepreneur is able to obtain the expected profit, and (4) renewal of packaging space, which mandates that employees would work more efficiently. From this dedication, kacang disco kecak mama felt the benefits of the increased order that was originally only 200pcs of peanut wrappers in a day increased to 400 pcs, causing they decided to increase the number of employees who originally only 25 people to 40 people, and employees feel comfortable with a well-organized work environment. With the increase in orders this means kacang disco kecak mama?s income has increased.